Discurso ambiental, política de turismo e exclusão social: uma análise sobre o excursionismo na praia de Jacumã/PB. - Machado, Adjane de Araújo (2012)
Making reference to the practice of excursions on the Jacumã beach, located in the Conde city, the proposal this study aims to analyze the relation between environmental discussion, tourism politics and social exclusion. The environmental discussion permeates the recent developmental concepts that surround academic and politics discussions about tourism, once the activity has been discussed from the perspective to embrace socioeconomic, cultural, politics and ecological factors in its development. Tourism politics refers to the role of the government as creator and promoter of development of activity supported by value concepts, particularly, in regards to employment generation and incomes for the location. Social exclusion refers to the case study about excursions on the Jacumã/PB beach, that during a long time it was reference of leisure for the popular excursions, known as farofeiros , but according its recent tourist attractiveness received a flow of tourist excursion that are different of lower classes by the distinctions consumptions. In this scenario of social distinctions, the governmental of Conde implements a politics, supported by law that charges a tourism tax for access of excursions in local beaches, reflecting the enjoyment of leisure of the members of disadvantaged social groups, it means the farofeiros . From this question, started with the idea about environmental racism, once the tourism politics began to affect in a disproportionate way the social groups involved with the leisure and tourism local. For the investigation was conducted an empirical research on the Jacumã beach, to know the opinion about tourism politics of different people who are part of social scenario of the beach, as well as research with the farofeiros and tourists in order to realize a comparative analyze of dynamic socio-spatial that defines the beach as the leisure space for two groups. Conclude with this research that the creating of tourism politics above, in addition to privatize, disrespects the rights of enjoyment of public space for a significant number of citizen.